2020
DOI: 10.1097/nmc.0000000000000634
|View full text |Cite
|
Sign up to set email alerts
|

Grief among Neonatal Intensive Care Nurses

Abstract: Background: Nurses working in the high-stress environment of the neonatal intensive care unit (NICU) are at high risk of experiencing grief after death of a baby. Design: Using a quantitative cross-sectional design, a convenience sample of nurses working in a Level IV NICU in Northern California, United States completed online surveys. Level of grief among NICU nurses, perceptions of grief support available at their institution, and past and future grie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 23 publications
0
27
0
4
Order By: Relevance
“…Neonatal intensive care patients are more vulnerable than other patient groups, their risk of injury is higher, and their care needs are complex. For this reason, it was reported that sadness experienced by nurses in neonatal intensive care units may be different and more intense than nurses working in other units (Rodriguez et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neonatal intensive care patients are more vulnerable than other patient groups, their risk of injury is higher, and their care needs are complex. For this reason, it was reported that sadness experienced by nurses in neonatal intensive care units may be different and more intense than nurses working in other units (Rodriguez et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It was seen from nurses’ statements that they empathized with the family. After long-term hospitalizations, the relationship between nurses and parents improves; nurses support the family on many issues and provide emotional support (Rodriguez et al., 2020). As a result, emotions experienced by nurses while giving bad news to the family were expected.…”
Section: Discussionmentioning
confidence: 99%
“…Literature suggests that healthcare professionals experience grief after a patient death in ways that are similar to personal losses (15,20,29). However, a recent NICU nursing study, using the Revised Grief Experience Survey, demonstrated lower levels of grief in bedside nurses when compared to family caregivers (36). In relation to patient suffering, grief may be compounded by feelings of guilt and powerlessness when providing what is perceived as futile care to patients (29,37).…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 20 Among healthcare providers, grief following a patient’s death may correlate with emotional exhaustion, burnout, and reduced job satisfaction. 21 , 22 Strategies for addressing grief include helping patients and families prepare for death through advance care planning, responding to and validating emotional reactions, addressing anticipatory grief, and on the part of healthcare providers, being aware of personal grief reactions and engaging in self-care. 18 Such interventions are within the scope of palliative care specialists’ practice making them particularly well-qualified to establish and lead hospital bereavement efforts, instruct care providers on how to support bereaved families, and counsel providers in coping with their own grief.…”
Section: Discussionmentioning
confidence: 99%